Missouri's lack of mental health care means patients suffer from over-prescribed anxiety meds - Coalition, Benzodiazepine Information (Benzodiazepine Information Coalition, 2021)
We spoke with Alex Smith for his article NPR Kansas City article about prescribed benzodiazepine issues: Missouri had the 4th highest rate in the country of residents taking benzodiazepines, and that was before the pandemic amped up anxiety. Experts say that long term use of these medications can cause lasting problems for patients. When Emily […]